2019
DOI: 10.1002/mgg3.801
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic variations of inflammatory biomarkers with susceptibility and severity of obstructive sleep apnea

Abstract: Background Obstructive sleep apnea (OSA) increases health risks of cardiovascular disease and stroke. Both genetic factors and environmental exposures contribute to the occurrence of OSA. The purpose of this study was to determine the role of four functional inflammatory single nucleotide polymorphisms (SNPs) (VWF rs1063856, IL‐6 rs1800796, TNF rs1800629, and CRP rs2794521) in the susceptibility and severity of OSA. Methods A case–control study of OSA among Chinese population was conducted. Genotyping was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…For us, genetic variants for the cytochrome P450 1A 2 (CYP1A2), the main system responsible for caffeine metabolism, and variants for pro-inflammatory cytokines should be investigated. Indeed, mutations on the CYP1A2 gene were recently shown to influence abstract reasoning in a large population (1374 participants) under free caffeine intake in everyday life [36], and genetic variations of inflammatory cytokines IL-6 and TNF-α have been associated in several studies with sleep disturbances [37] and susceptibility and severity of obstructive sleep apnea [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For us, genetic variants for the cytochrome P450 1A 2 (CYP1A2), the main system responsible for caffeine metabolism, and variants for pro-inflammatory cytokines should be investigated. Indeed, mutations on the CYP1A2 gene were recently shown to influence abstract reasoning in a large population (1374 participants) under free caffeine intake in everyday life [36], and genetic variations of inflammatory cytokines IL-6 and TNF-α have been associated in several studies with sleep disturbances [37] and susceptibility and severity of obstructive sleep apnea [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…We planned in our future studies to analyze A2A receptors density, function or gene expression in human blood in relation with the three genotypes of rs2298383, rs4822492 and rs5751876 ADORA2A variants. It will be interesting in future studies to investigate in a large population of European ancestry sleep duration and risk of sleep complaints and disorders concomitantly with multiple candidate SNP including dopamine-and cytokines-related genes [39,46], and genes involved in the pharmacokinetic and pharmacodynamic of caffeine effects [35,36]. Also, analysis of changes in A2A receptors density, function or gene expression in human granulocytes under low and high doses of caffeine consumption will aid in understanding the relationship between genetic mutations and sleep complaints and disorders, and will have implications for the treatment of sleep complaints [47].…”
Section: Discussionmentioning
confidence: 99%
“…В большинстве опубликованных ранее работ по исследованию генетических детерминант СОАС и его ССО исследовались в основном гены, ответственные за экспрессию воспалительных цитокинов. В работе Zhang Z, et al (2019) была выявлена значимая ассоциация с сердечно-сосудистыми исходами генов, кодирующих интерлейкин-6, фактор некроза опухоли-α и С-реактивный белок [21]. С учетом важной роли окислительного стресса в патогенезе СОАС в зоне повышенного внимания исследователей оказались и вероятные генетические предикторы медиаторов окислительного стресса.…”
Section: Discussionunclassified
“…Van Eyck et al 43 demonstrated that OSAS does not contribute significantly to CRP levels in obese children and adolescents. This discrepancy in the levels of inflammatory markers and OSA might reflect differences in genetic background, environmental exposure, or disease phenotypes 44 . Kheirandish‐Gozal et al 45 reported that four functional single‐nucleotide peptides (SNPs) of von Willebrand factor, TNF‐α, CRP, and interleukin‐6 (IL‐6) genes are significantly associated with increased susceptibility to OSA.…”
Section: Discussionmentioning
confidence: 99%